Women and Work in Premodern Europe - Bailey, Merridee L., author.
1 online resource (256 pages)
Keywords: "This book re-evaluates ideas of work and of what work could entail for women in premodern Europe, spanninga period from roughly 1100-1800 CE. Its broad-based yet thematically focused approach provides an opportunity to explore and understand the diversity of premodern women's experiences of work, the nature of these women's working relationships with both men and other women, and the various cultural modes in which those experiences and relationships could be represented and deployed."--Provided by publisher.